2020
DOI: 10.1109/access.2020.3007786
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Change and Landscape Pattern Variation of Eco-Environmental Quality in Jing-Jin-Ji Urban Agglomeration From 2001 to 2015

Abstract: Identifying the changes and relationships between regional eco-environment quality and landscape pattern in an urban agglomeration have a great significance in realizing sustainable development goal. However, limited research has been performed to understand the spatiotemporal change of ecoenvironment quality, the variation of landscape pattern, and their relationship in an urban agglomeration. This study selected the Jing-Jin-Ji (JJJ) urban agglomeration as the study area. A comprehensive index, the remote se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 66 publications
0
36
0
Order By: Relevance
“…It includes the landscape metric parameters e.g., the number of patches that can determine the number of subpopulations in a spatially dispersed population or metapopulation for species that are specifically associated with a particular habitat type (McGarigal 1994). Forest fragmentation at the microlandscape level is indicated by NP ≥ 1 (Ji et al 2020) and all study sample sites showed forest fragmentation, with an NP value ≥ 1. The two sample sites with the lowest forest NP values were S04 (Pongpok) and S07 (Batu Sahulu).…”
Section: Landscape Structure At the Sample Sitesmentioning
confidence: 99%
“…It includes the landscape metric parameters e.g., the number of patches that can determine the number of subpopulations in a spatially dispersed population or metapopulation for species that are specifically associated with a particular habitat type (McGarigal 1994). Forest fragmentation at the microlandscape level is indicated by NP ≥ 1 (Ji et al 2020) and all study sample sites showed forest fragmentation, with an NP value ≥ 1. The two sample sites with the lowest forest NP values were S04 (Pongpok) and S07 (Batu Sahulu).…”
Section: Landscape Structure At the Sample Sitesmentioning
confidence: 99%
“…The Beijing-Tianjin-Hebei or Jing-Jin-Ji region is located in the northeastern part of mainland China (Figure 1 2 . The Jing-Jin-Ji region is one of the most heavily urbanized and industrialized regions in China [47,48]. With a population of more than 100 million, the economy of the study area contributed 8.5% of China's GDP in 2019.…”
Section: Study Areamentioning
confidence: 99%
“…The study area extends from 113° 4′ E to 119° 53′ E and from 36° 1′ N to 42° 37′ N, covering an area of approximately 216,000 km 2 . The Jing-Jin-Ji region is one of the most heavily urbanized and industrialized regions in China [47,48]. With a population of more than 100 million, the economy of the study area contributed 8.5% of China's GDP in 2019.…”
Section: Study Areamentioning
confidence: 99%
“…In the past decade, a series of high-resolution satellites have launched a new era of satellite remote sensing. The acquisition of high-resolution remote sensing images is more convenient, with high spatial resolution and rich detailed information of ground features, which has important and far-reaching significance for the monitoring of land-use change [6][7][8], building change [9,10], vegetation ecological monitoring [11][12][13], disaster monitoring and evaluation [14,15], and coastline change [16]. A series of classical remote sensing change detection methods developed in the past few decades have also been applied in the change detection of high-resolution images.…”
Section: Introductionmentioning
confidence: 99%
“…represents the average value of the spectral band. The spectral shape difference image calculated according to SGD algorithm Eq (13,14).…”
mentioning
confidence: 99%